Near-Infrared Soliton Mode-Locked Thulium Doped Fibre Laser Using WS2-ZnO Composite Material as Saturable Absorber - Ahmad, Harith; Monajemi, Hadieh; Samion, Muhamad Zharif; Yusoff, Norazriena; Ismail, Mohammad Faizal; Yasin, Mohamad; Bayang, Leonard (Institute of Electrical and Electronics Engineers (IEEE), 2019)
The generation of a highly stable passive mode locking laser is realized in a thulium doped fibre laser using a WS2-ZnO composite as a saturable absorber. Soliton mode locking pulses are generated with a central wavelength of 1936 nm and full-width half maximum (FWHM) of 3.06 nm. The first order Kelly's side band is located at around 5.65 nm from the central wavelength which gives the calculated pulse width value of 1.26 ps. This value corresponds well with the measured pulse width of 1.27 ps using the autocorrelator. The output power of the laser is around 0.44 mW with the peak power of 29.7 W and repetition rate of 9.96 MHz. This laser set-up is highly robust and realizes highly stable laser pulses in the mid-IR wavelength range for a multitude of applications. © 2009-2012 IEEE.